School Environment Structuring Strategy Through the Adiwiyata Program at MTsN Penukal Abab Lematang Ilir Regency - Marlina, Leni; Zainuri, Ahmad; Gani, Yasir Muslim; Annur, Saipul (Jurnal Visionary : Penelitian dan Pengembangan dibidang Administrasi Pendidikan, 2025)
MTsN in Penukal Abab Lematang Ilir Regency is a school whose curriculum and learning process emphasizes the principle of Adiwiyata, which prioritizes educational values and the formation of students' character to love the environment. This is reflected in the many environmental literacy programs that aim to provide students with ecological care through the Adiwiyata program. This study aims to analyze the implementation of the adiwiyata program, find out the supporting factors for the implementation of the adiwiyata program, and find out the factors that hinder the implementation of the adiwiyata program in MTsN Penukal Abab Lematang Ilir Regency. This type of research is field research with a qualitative approach, and the research design used is a phenomenon and multi-case research related to school environment management strategies, the implementation of adiwiyata program activities, and the involvement of students and teachers in implementing the adiwiyata program. The subjects of this research are all those involved in environmental planning programs, adiwiyata programs, and school principals. The data collection method is done through observation, documentation, and interviews. This study results in the conclusion that the implementation of the Adiwiyata program in MTsN Penukal Abab Lematang Ilir Regency is by the Adiwiyata Guidebook, based on environmentally friendly policies, environment-based curriculum, participatory environmental activities, and management of environmentally friendly infrastructure, and supporting factors for the implementation of the Adiwiyata program majority of school residents, as well as the inhibiting factor for the implementation of the Adiwiyata program, is the lack of fund allocation,Â  lack of public awareness in maintaining environmental cleanliness, lack of socialization from the ecological agency about the adiwiyata program.Keywords: School Environment Arrangement, Adiwiyata Program.